Synergistic effect of the Bacillus thuringiensis toxins CryIAa and CryIAc on the gypsy moth, Lymantria dispar. - Lee, M K (1996)
The insecticidal activity of toxins CryIAa, CryIAb, and CryIAc against Lymantria dispar (gypsy moth) and Bombyx mori (silkworm) was examined by force-feeding bioassays. Toxin CryIAa exhibited higher toxicity than toxins CryIAb and CryIAc for L. dispar and B. mori. To evaluate possible synergism among these toxins, bioassays were performed with mixtures of CryIAa and CryIAb, CryIAb and CryIAc, and CryIAa and CryIAc. Expected toxicity was calculated from the activity of each individual toxin and its proportion in the mixture by using the equation described by Tabashnik (B. E. Tabashnik, Appl. Environ. Microbiol. 58:3343-3346, 1992). Observed 50% growth-inhibitory doses were calculated from mixing experiments by probit analysis. In L. dispar bioassays, synergism was observed with a mixture of CryIAa and CryIAc while a mixture of CryIAa and CryIAb exhibited an antagonistic effect. No synergistic effect on B. mori was observed with any toxin combination. Voltage clamping assays of isolated L. dispar midguts also demonstrated that the mixture of CryIAa and CryIAc induced a greater slope of inhibition of short circuit current than did other toxin combinations.